Rheumatic Heart Disease Treatment Cascade in Uganda - Chris, T. Longenecker; Stephen, R. Morris; Aliku, Twalib O.; Andrea, Beaton; Marco, A. Costa; Kamya, Moses R.; Kityo, Cissy; Lwabi, Peter; Mirembe, Grace; Nampijja, Dorah; Rwebembera, Joselyn; Craig, Sable; et al. (Circulation: Cardiovascular Quality and Outcomes, 2017)
Background Rheumatic heart disease (RHD) is a leading cause of premature death and disability in low-income countries; however, few receive optimal benzathine penicillin G (BPG) therapy to prevent disease progression. We aimed to comprehensively describe the treatment cascade for RHD in Uganda to identify appropriate targets for intervention. Methods and Results Using data from the Uganda RHD Registry (n=1504), we identified the proportion of patients in the following care categories: (1) diagnosed and alive as of June 1, 2016; (2) retained in care; (3) appropriately prescribed BPG; and (4) optimally adherent to BPG (>80% of prescribed doses). We used logistic regression to investigate factors associated with retention and optimal adherence. Overall, median (interquartile range) age was 23 (15–38) years, 69% were women, and 82% had clinical RHD. Median follow-up time was 2.4 (0.9–4.0) years. Retention in care was the most significant barrier to achieving optimal BPG adherence with only 56.9% (95% confidence interval, 54.1%–59.7%) of living subjects having attended clinic in the prior 56 weeks. Among those retained in care, however, we observed high rates of BPG prescription (91.6%; 95% confidence interval, 89.1%–93.5%) and optimal adherence (91.4%; 95% confidence interval, 88.7–93.5). Younger age, latent disease status, and access to care at a regional center were the strongest independent predictors of retention and optimal adherence. Conclusions Our study suggests that improving retention in care—possibly by decentralizing RHD services—would have the greatest impact on uptake of antibiotic prophylaxis among patients with RHD in Uganda.